Terrain-aware traverse planning for a Mars sample return rover. (17th November 2021) - Hedrick, G.; Gu, Y.
Abstract : NASA and ESA are proposing to retrieve samples from Mars with a rover that will need to drive long distances, beyond what is seen on images from previous downlinks, to complete its mission in less than 200 Martian days. This paper proposes a planning method to support Mars Sample Return by integrating terrain information into the planning phase. The first step consists of predicting rover slip and drive speed using orbital data. When tested with Mars data, slip ranges are predicted and an expected velocity map is successfully drawn. The second step involves planning the traverse for the driving objective of a sol, based on the map of expected slip and drive speed. While driving, the rover monitors the terrain by converting its wheel slip and speed into terrain information, projected forward to confirm or refute predicted behavior, update the map and replan if necessary. Simulation showed successful map updates given new information and replanning when needed. If monitoring is insufficient to confirm traversability, a third step describes an instrument would be deployed to compute intrinsic terrain parameters, information then propagated ahead to update and replan if necessary. Experiments showed results close to the expected parameters of the tested soils. GRAPHICAL ABSTRACT: UF0001